"I Felt Guilty for Being So Happy": Narrative Expressions and Management of Postdivorce Ambivalence. Issue 3 (3rd July 2018) - Winchester, Daniel; Spencer, J. William; Baird, Denise M
ABSTRACT: Scholars have highlighted ambivalence as a central feature of experiences of divorce and its aftermath and discussed ambivalence as an important issue for divorcees in adjusting to their new status. While most of this scholarship assesses postdivorce ambivalence as a psychological phenomenon to be addressed therapeutically, this study analyzes postdivorce ambivalence as an interpretive problem to be addressed sociologically. Following Merton's (1976) insight that ambivalence be viewed as rooted in culture and social structure as well as individual psyche, we use a narrative analytic perspective to examine how divorcees both discursively express and interpretively manage their ambivalence. We then consider some of the more general cultural discourses—such as images of marriage and divorce—that shape or condition these narratives. Ultimately, we argue that conflicting stances toward marriage in the wider U.S. culture are at once important sources of postdivorce ambivalence and significant interpretive resources for its discursive management.